TYPES OF PROCESS IN PITBULL’S SONG LYRICS - Florentina A. S; Sri Minda Murni (State University of Medan, 2013)
ABSTRACT This article deals with types of process in Pitbull’s song lyrics. The objectives of this article is to find the types of process in Pitbull’s song lyrics, the dominant process in Pitbull’s song lyrics, and to investigate the implication of dominant process with hedonictics life style. Fiftheen songs were taken as the data and analyzed by descriptive qualitative method. The findings of this article showed that six types of process are found in the Pitbull’s song lyrics. The most dominant process was mental process, it implied that the songs lyrics in Pitbull’s song expressed hedonistics life style which are dealing with the process of sensing which covering thinking, feeling, and emotions which happened inside human beings. Keywords: process, song, Pitbull, descriptive qualitative, hedonistics